A FIRST VERSION OF A BRIEF ANXIETY SCALE BASED ON THE INVENTORY OF SITUATIONS AND RESPONSES OF ANXIETY (I.S.R.A.) - Martínez-Sánchez, Francisco; Cano-Vindel, Antonio; Castillo Precioso, Jose C.; Sánchez García, Jose A.; Ortiz Soria, Beatriz; Gordillo del Valle, Ester (Anales de Psicología / Annals of Psychology)
In this paper a preliminary version of a brief anxiety scale, extracted from the Inventory of Situations and Responses of Anxiety, I.S.R.A. (Miguel Tobal & Cano Vindel, 1986, 1988, 1994) is presented. This scale tries to assess the general level of anxiety in a simple way. Starting from the 24 (7 cognitive, 10 physiological, and 7 motor) responses of anxiety -all of them included in the ISRA-, some items were reformulated, instructions were changed, the way of response was modified, and finally 17 items following a factorial criterium were selected. This paper describes the factorial structure of the scale, and the general anxiety levels in different groups, as well as the correlation with the S.T.A.I., in a sample of 238 subjects (control group, patients with anxiety disorders and patients with somatic diseases). The results show that the two clinical groups are significantly higher than the normal group in the general level of anxiety; as well as, the somatic group is higher than the anxiety disorders group. Factor analysis support the tridimensional model of anxiety (cognitive, physiological and motor anxiety responses). Finally, this paper is concluded showing that this scale is a useful measure to assess anxiety responses.